Persepsi Mahasiswa Akuntansi dan Mahasiswa Manajemen terhadap Profesionalitas Pendidikan Akuntansi - Desmiyawati Desmiyawati; Julita Saidi (Jurnal Akuntansi dan Bisnis, 2006)
This study investigates whether undergraduate accounting education is more successful at instilling in accounting students a sense of responsibility to financial statement users than management students in Faculty of Economic of Riau University. The responses from 296 students were analyzed by using t-test. We find that senior accounting students oppose earnings management stronger than junior accounting students. We also find that senior accounting students opposed earnings management more stronger than senior students do in management disciplines. The senior accounting students' responses suggest that they are more strongly opposed to omitting or misstating financial information than junior accounting students and senior management students. The management students appear to have become less inclined to disclose potentially sensitive information than accounting students. The management students appear to believe stronger than the accounting students that Indonesia companies are burdened by complex accounting rules and that companies are forced to reveal unnecessary information. These results are consistent with socialization process taking place wherein accounting students learn to give priority to financial statement users' need, while students majoring in management disciplines come to identify more closely with the goals of corporate managers (Clikeman & Henning, 2000).